2019
DOI: 10.1097/pra.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Lifetime Suicide Attempts With Anxiety Disorders in Patients With Bipolar Disorder

Abstract: The association of lifetime suicidal behaviors with anxiety disorders (ADs) in patients with bipolar disorder (BD) has been controversial. In this study, we hypothesized that certain types of ADs were related to the occurrence of past suicide attempts (SAs) independent of the severity of the BD, including the presence of past affective episodes. Lifetime diagnoses of BD and ADs were assessed using the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The most common comorbid anxiety conditions are panic disorder, social anxiety and generalised anxiety disorders; however, multimorbidity is also common [ 6 ]. Co-morbid anxiety in bipolar disorder is associated with greater current symptom severity, increased impairment and increased risk of mood episodes [ 8 ] and lifetime suicide attempts [ 9 ]. Studies have also found that anxiety in bipolar disorder is also associated with lower quality of life, earlier relapse and diminished role function, with a greater impact also being found with the presence of multiple co-occurring anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The most common comorbid anxiety conditions are panic disorder, social anxiety and generalised anxiety disorders; however, multimorbidity is also common [ 6 ]. Co-morbid anxiety in bipolar disorder is associated with greater current symptom severity, increased impairment and increased risk of mood episodes [ 8 ] and lifetime suicide attempts [ 9 ]. Studies have also found that anxiety in bipolar disorder is also associated with lower quality of life, earlier relapse and diminished role function, with a greater impact also being found with the presence of multiple co-occurring anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Suicidal ideation is common in both PTSD and anxiety-related disorders. Bipolar disorder is strongly associated with suicide attempts, and this is amplified in those patients with comorbid PTSD and social anxiety disorder 25 . The risk of suicide attempts is elevated in patients with panic disorder, PTSD, and generalized anxiety disorder even in the absence of a comorbid mood disorder, although the latter substantially increases risk 26 …”
Section: Epidemiologic Aspectsmentioning
confidence: 99%
“…Bipolar disorder is strongly associated with suicide attempts, and this is amplified in those patients with comorbid PTSD and social anxiety disorder. 25 The risk of suicide attempts is elevated in patients with panic disorder, PTSD, and generalized anxiety disorder even in the absence of a comorbid mood disorder, although the latter substantially increases risk. 26 Risk Factors for Posttraumatic Stress Disorder and Anxiety-Related Disorders Several factors are related to both resilience and vulnerability to development of PTSD after trauma exposure.…”
Section: Prevalence Of Posttraumatic Stress Disordermentioning
confidence: 99%
“…20% of people with bipolar disorder have a lifetime diagnosis of social anxiety disorder (Pavlova et al 2015 ), and 10% of people with bipolar disorder still meet diagnostic criteria for social anxiety disorder when they are euthymic (Pavlova et al 2017 ). Several investigations have linked social anxiety disorder with increased rates of suicidal ideation and behaviour (Perroud et al 2007 ; Kocabas et al 2019 ; Amuk and Patel 2020 ; Masi et al 2021 ), as well as with substance use problems (Yapici Eser et al 2018 ) in people with bipolar disorder. These associations were stronger for social anxiety disorder than for any other anxiety disorder (Perroud et al 2007 ; Yapici Eser et al 2018 ; Kocabas et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%